Implementation of Deep Learning and Utilization of Artificial Intelligence at SMPN 15 Mataram - Dhea Kapril Amanda; Bila Anggraini; Mohamad Mustari (Penerbit Hellow Pustaka, 2025)
This study aims to provide a detailed description of the implementation of deep learning and the utilization of Artificial Intelligence (AI) in the learning process at SMPN 15 Mataram. This research is based on the demands of 21st-century education, which emphasize critical thinking, creativity, collaboration, and digital literacy. A descriptive qualitative method was employed, with data collected through direct observation of classroom activities and interviews with subject teachers. The findings reveal that deep learning has been implemented through various learning strategies, including classroom discussions, group collaboration, interactive questioning, and project-based learning assignments that encourage students to think independently and develop problem-solving skills. However, the use of AI in the learning process remains limited. This is due to the school policy that restricts students from using personal mobile devices during lessons, resulting in AI mainly being utilized by teachers, particularly for preparing teaching materials, searching for references, and planning instructional activities.Several challenges also hinder the optimization of AI integration, including limited technological facilities, uneven internet access, insufficient digital literacy skills among teachers and students, and the lack of training related to AI-based learning tools. Therefore, it can be concluded that deep learning is already being practiced effectively in SMPN 15 Mataram, supporting the development of students’ competencies. However, the integration of AI still requires improvement through enhanced technological support and the provision of digital literacy training for both teachers and students.